Mycotic Mastitis in Ruminants - Yanuartono, Yanuartono; Nururrozi, Alfarisa; Indarjulianto, Soedarmanto; Raharjo, Slamet; Purnamaningsih, Hary (Faculty of Animal Science, Universitas Brawijaya, 2019)
Mastitis is a disease caused by a wide variety of microorganisms that causes large economical loses and damages to the dairy industry by decreasing milk production and through increasing costs of antibiotic treatment and culling. In spite of the prevalence of mycotic mastitis is usually very low as compared to other agents of mastitis, but it has significantly increased during the last decade In recent years, fungal agents have been frequently reported among the causative agents for mastitis. Though moulds and yeasts are widely distributed in nature, only the yeasts are usually implicated as the cause of mycotic mastitis infections in ruminants. Given the importance of the disease, especially in terms of economic losses, in this short article we try to make a review to help practitioners and farmers in controlling and minimizing the incidence of mycotic mastitis.